1971
DOI: 10.1007/bf00285186
|View full text |Cite
|
Sign up to set email alerts
|

Differential fluorescent staining of Drosophila chromosomes with quinacrine mustard

Abstract: The polytene and mitotic chromosomes of D. melanogaster, D. simulans, D. ananassae, and D. virilis were stained with the fluorescent dye, quinacrine mustard (QM). In all these species except D. ananassae, we have detected speciesspecific chromosomal loci which exhibit an extremely brilliant fluorescence. Most, but not all, of the brilliantly fluorescing areas are located in heterochromatic chromosome regions. Cytochemical and chemical methods have been employed to demonstrate that the brilliant fluorescence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…The observation of a quinacrine-bright area in D. virilis at the base of chromosome four is consistent with the results of ADKISSON et al ( 1971 ). However, ADKISSON and colleagues reported only a single band, and presumably did not observe the doublet.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The observation of a quinacrine-bright area in D. virilis at the base of chromosome four is consistent with the results of ADKISSON et al ( 1971 ). However, ADKISSON and colleagues reported only a single band, and presumably did not observe the doublet.…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, it has been demonstrated that quinacrine can be used to localize certain AT-rich satellite DNA sequences in metaphase chromoso· mes (PARDUE 1973;ADKISSON et al 1971;GALL et al 1971).…”
Section: Relationship Of Q-bands To Satellite Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that quinacrine renders some heterochromatic regions brightly fluorescent (Caspersson et al 1969;Adkisson et al 1971). More recently, Ellison and Barr (1972) demonstrated bright quinacrine fluorescence in Samoaia leonensis chromosomes in areas of adenineand thymine-rich DNA.…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster (Rodriguez-Alfageme et al, 1976). This study noted a correlation between the chromosomal sites that fluoresce most intensely with anti-Dl anti bodies and the sites known to fluoresce most intensely with quinacrine (Vosa, I97O;Adkisson et al, 1971;Ellison and Barr, 1972;Mayfield and Ellison, 1975;Hochman, 1976). A more carefully controlled follow-up investigation revealed that, under conditions that minimize nonspecific antibody interactions, D1 is widely distributed throughout the cytoplasm and nucleus, present in many chromomeras, but most abundant in chromosomal sites that contain the A-T rich satellite DNA of buoyant density 1.672 g ml ^ (Rodriguez-Alfageme et al, 1980).…”
Section: Protein D1mentioning
confidence: 90%